Hubungan Tingkat Pengetahuan Ibu terhadap Kelengkapan Imunisasi pada Anak di Wilayah Puskesmas Payung Sekaki - Thania Dwi Yanti; Tuti Alawiyah; Tia Wulandari; Syavira Orizka; Febby Wilanda; Echa Rezkya; Luthfi Fadilatul; Linda Andra Pita; Desi Nindya Kirana (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2026)
Immunization is an effective preventive measure that protects children from various infectious diseases that can be prevented by immunization. However, the completeness of immunization in children remains a public health problem in several areas, including the working area of ​​the Payung Sekaki Community Health Center. A factor that influences the completeness of immunization is the level of maternal knowledge. This study aims to determine the relationship between the level of maternal knowledge and the completeness of immunization in children in the Payung Sekaki Community Health Center area. This study used a quantitative method with a cross-sectional design. The number of respondents was 15 mothers with children aged 12–23 months, using a purposive sampling technique. Data were collected through questionnaires to measure the level of maternal knowledge and KIA book records to determine the status of completeness of children's immunization. Data analysis was carried out univariate and bivariate using the Chi-Square test. The study showed that most mothers had a good level of knowledge (46.7%) and most children had received complete basic immunization (60.0%). The results of the Chi-Square test showed a significant relationship between the level of maternal knowledge and the completeness of children's immunization with a p value of 0.041 (p < 0.05). The conclusion of this study is that there is a significant relationship between maternal knowledge and the completeness of immunizations in children in the Payung Sekaki Community Health Center area. Therefore, improving health education for mothers is necessary to increase the coverage of complete basic immunizations.